A structured process for unmet clinical need analysis for medical device innovation in India: early experiences. Issue 3 (28th May 2015) - Chaturvedi, Jagdish; Logan, Andrew; Narayan, Girish; Kuttappa, Shakuntala
Abstract : It is estimated that approximately 75% of medical devices and diagnostics come to India from imports. A WHO report on medical devices highlighted that most devices present in developing countries have been designed for use in developed countries. Consequently, when these medical devices are implemented in India, they are either unaffordable or are maladapted to fit the complex healthcare ecosystem. A strong need exists to develop technologies that are intentionally designed to suit the Indian healthcare system. To address these issues, we have applied a modified version of the biodesign process, originally developed by Stanford University, to identify unmet clinical needs in the field of emergency medicine at a tertiary referral hospital in southern India. Since the biodesign process was originally created to identify unmet needs in a more mature Medtech ecosystem, we have altered its implementation to make it more suitable to the evolving Medtech ecosystem that prevails in India. At the completion of 2 months of clinical immersion by a multidisciplinary team, 100 unmet needs with significant negative outcomes were identified. The team then took all the need statements collected during the period of the clinical immersion and applied four rounds of precalibrated filters to arrive at the top 10 most compelling clinically validated needs that would be selected for the phase of invention. In this article, we present our reasons for making modifications to the biodesign process, our results and our experiences while implementing this process in an Indian healthcare system.